Baseline metal concentrations in Paramoera walkeri from East Antarctica - Palmer, AS; Snape, I; Stark, JS; Johnstone, GJ; Ashley Townsend (2006)
Remediation of the Thala Valley waste disposal site near Casey Station, East Antarctica was conducted in the austral summer of 2003/2004. Biomonitoring of the adjacent marine environment was undertaken using the gammaridean amphipod Paramoera walkeri as a sentinel species [Stark, J.S., Johnstone, G.J., Palmer, A.S., Snape, I., Larner, B.L., Riddle, M.J., in press, doi:10.1016/j.marpolbul.2006.05.020. Monitoring the remediation of a near shore waste disposal site in Antarctica using the amphipod Paramoera walkeri and diffusive gradients in thin films (DGTs). Marine Pollution Bulletin and references therein]. Determination of uptake of metals and hypothesis testing for differences that could be attributed to contamination required the establishment of baseline metal concentrations in P. walkeri. Baseline metal concentrations from two reference locations in the Windmill Islands are presented here. P. walkeri was a found to be a sensitive bioaccumulating organism that recorded spatial and temporal variability at the reference sites. Measurement of metals in P. walkeri required the development of a simple digestion procedure that used concentrated nitric acid. For the first time, rare earth metals were determined with additional clean procedures required to measure ultra low concentrations using magnetic sector ICP-MS. Certified and in-house reference materials were employed to ensure method reliability. Â© 2006 Elsevier Ltd. All rights reserved.